Design optimization of the landing slope of a ski jumping hill - Seo, K.; Nihei, Y.; Shimano, T.; Ohgi, Y. (Third International Congress on Sports Science Research and Technology Support, icSPORTS 2015, 2015)
This paper describes a procedure for optimizing the design of the landing slope of the Zao jumping hill. The concept behind the design of the landing slope is that the landing slope should enable the spectators to witness an exciting spectacle, that the jumpers can land safely, and that it can be constructed with minimum cost. We regard these features as objective functions. The findings can be summarized as follows: it is possible to control the objective functions by changing the profile of the landing slope; there is not a unique optimal design solution, but the Pareto optimal solutions; a landing slope that gives safety on landing is almost equivalent to a landing slope that produces differences in the flight distance due to differences the jumpers` skill levels; there is a trade-off between the length of the flight distance and safety on landing; the construction cost is influenced by the horizontal distance between the edge of the take-off table and the K-point. The developed procedure would be applicable not only to Zao in Yamagata city, but also to all ski jumping hills in the world.